Inhibition of GCN2 Alleviates Cardiomyopathy in Type 2 Diabetic Mice via Attenuating Lipotoxicity and Oxidative Stress - Juntao Yuan; Fang Li; Bingqing Cui; Junling Gao; Zhuoran Yu; Zhongbing Lu (Antioxidants, 2022)
Diabetic cardiomyopathy (DCM) is a kind of heart disease that affects diabetic patients and is one of the primary causes of death. We previously demonstrated that deletion of the general control nonderepressible 2 (GCN2) kinase ameliorates cardiac dysfunction in diabetic mice. The aim of this study was to investigate the protective effect of GCN2iB, a GCN2 inhibitor, in type 2 diabetic (T2D) mice induced by a high-fat diet (HFD) plus low-dose streptozotocin (STZ) treatments or deletion of the leptin receptor (db/db). GCN2iB (3 mg/kg/every other day) treatment for 6 weeks resulted in significant decreases in fasting blood glucose levels and body weight and increases in the left ventricular ejection fraction. GCN2iB treatment also attenuated myocardial fibrosis, lipid accumulation and oxidative stress in the hearts of T2D mice, which was associated with decreases in lipid metabolism-related genes and increases in antioxidative genes. Untargeted metabolomics and RNA sequencing analysis revealed that GCN2iB profoundly affected myocardial metabolomic profiles and gene expression profiles. In particular, GCN2iB increased myocardial phosphocreatine and taurine levels and upregulated genes involved in oxidative phosphorylation. In conclusion, the data provide evidence that GCN2iB effectively protects against cardiac dysfunction in T2D mice. Our findings suggest that GCN2iB might be a novel drug candidate for DCM therapy.